An Overview About the Security Architecture of the Mobile Operating System iOS - Philip, Jithu; Raju, Merin (Indian Journal of Computer Science, 2019)
The use of mobile operating systems is rapidly increasing as the number of smartphone users is increasing day by day. iOS is one of the most popular and widely used mobile operating systems in the world. This document describes an overview about the security features of iOS in its low-level system framework and in its user-level applications framework. The document discusses processes like how security is implemented in the core components of the system, how data protection and encryption is achieved, and how applications are secured by sandboxing.